Pendampingan di Bidang Informatika untuk Olimpiade Sains Kabupaten (OSK) - Klaudius Jevanda B.S.; R. Kristoforus Jawa Bendi; Latius Hermawan; Rafael Tomi Prakoso (J-ABDIPAMAS (Jurnal Pengabdian Kepada Masyarakat), 2019)
ABSTRACT This Community Service activity aims to provide assistance by utilizing IT for student of St. Yosef Lahat High School. The specific target expected from this activity is that students are able to understand and master the material on arithmetic, analytics, and algorithmic using IT-based technology to prepare for the 2018 OSK competition.The method of implementation carried out begins with determining partners, justifying the problems of partner, procedures carried out, work plans in community service activities. In its implementation, mentoring was carried out by a Team consisting of 3 lecturers and 1 student. The results of the questionnaire stated that this 2018 OSK competition assistance activity was useful for High School Student St. Yosef Lahat with an average of 78%. The mentoring output is High School Students St. Yosef Lahat understands  and master OSK questions including arithmetic, analytics, and algorithms with the best to prepare for the 2018 OSK competition.Keywords:  Assistance, OSK Competition, IT ABSTRAKKegiatan Pengabdian pada Masyarakat ini bertujuan untuk mengadakan pendampingan dengan memanfaatkan IT bagi siswa SMA St. Yosef Lahat. Target khusus yang diharapkan dari kegiatan ini adalah para siswa mampu memahami dan menguasai materi tentang aritmatika, analitika, dan algoritmika menggunakan teknologi berbasis IT guna persiapan lomba OSK 2018. Metode pelaksanaan yang dilakukan dimulai dari penentuan mitra, justifikasi persoalan mitra, prosedur yang dilakukan, rencana kerja dalam kegiatan pengabdian kepada masyarakat. Dalam pelaksanaannya, pendampingan dilakukan oleh Tim yang terdiri dari 3 dosen dan 1 mahasiswa. Hasil kuesioner menyatakan bahwa kegiatan pendampingan lomba OSK 2018 ini bermanfaat bagi siswa SMA St. Yosef Lahat dengan rata-rata sebesar 78 %. Luaran pendampingan ini adalah siswa SMA St Yosef Lahat memahami dan menguasai soal-soal OSK meliputi aritmatika, analitika, dan algoritmika dengan sebaiknya guna persiapan lomba OSK 2018. Kata Kunci: Pendampingan, Lomba OSK, IT